Implementasi Budaya Sekolah dalam Membentuk Profesionalisme Guru: Implementation of School Culture in Shaping Teacher Professionalism - Faqihudin, M. (Thawalib: Jurnal Kependidikan Islam, 2024)
The percentage of teachers teaching outside their field is 22.1%, with an average UKG test score of only 40.71, indicating a significant lack of professionalism. This is attributed to inadequate education, motivation, and dedication to their work. This research aims to explain the school culture at SD Islam Al-Azhar 14 Semarang used to shape professional teachers. The study employs qualitative methods with a case study approach, gathering data through interviews with principals, teachers, staff, and students. Data processing involves condensation, data presentation, and conclusions. Data validity is ensured through triangulation of techniques and sources. Results show that the communication culture at SD Islam Al-Azhar 14 Semarang emphasizes teacher professionalism through a unique system to build solids working relationships and maintain a strong culture. Integrated management aligned with the school's vision and mission, along with continuously updated structured planning, reflects discipline in adherence to regulations. External collaboration, including foundation oversight of principals and support from parents, strengthens synergy among teachers, principals, and staff. Conclusion: The implemented school culture helps in shaping teacher professionalism.